DNA-Aptamer Raised against Receptor for Advanced Glycation End Products Improves Survival Rate in Septic Mice. (9th August 2021) - Koga, Yoshinori; Sotokawauchi, Ami; Higashimoto, Yuichiro; Nishino, Yuri; Hashizume, Naoki; Kakuma, Tatsuyuki; Akiba, Jun; Tanaka, Yoshiaki; Matsui, Takanori; Yagi, Minoru; Yamagishi, Sho-ichi
Abstract : Despite remarkable scientific advances in the understanding of molecular mechanisms for sepsis, therapeutic options are far from satisfactory. High mobility group box 1 (HMGB1), one of the ligands of receptor for advanced glycation end products (RAGE), is a late mediator of lethality in septic mice. We have recently found that the DNA-aptamer raised against RAGE (RAGE-aptamer) significantly blocks experimental diabetic nephropathy and melanoma growth and metastasis. We examined the effects of RAGE-aptamer on sepsis score, survival rate, and inflammatory and oxidative stress responses in serum, peripheral monocytes, kidneys and livers of lipopolysaccharide- (LPS-) injected mice, and on LPS-exposed THP-1 cells. RAGE-aptamer inhibited the binding of HMGB1 to RAGE in vitro . RAGE-aptamer significantly (P = 0.002 ) improved sepsis score at 8 hours after LPS injection and survival rate at 24 hours (P < 0.01, 70%) in septic mice compared with LPS+vehicle- or LPS+control-aptamer-treated mice. RAGE-aptamer treatment significantly decreased expression of p-NF- κ B p65, an active form of redox-sensitive transcriptional factor, NF- κ B and gene or protein expression of TNF- α, IL-1 β, IL-6, and HMGB1 in serum, peripheral monocytes, and kidneys of septic mice in association with the reduction of oxidative stress and improvement of metabolic acidosis, renal and liver damage. LPS-induced oxidative stress, inflammatory reactions, and growth suppression in THP-1 cells were significantly blocked by RAGE-aptamer. Our present study suggests that RAGE-aptamer could attenuate multiple organ damage in LPS-injected septic mice partly by inhibiting the inflammatory reactions via suppression of HMGB1-RAGE interaction.